2012
DOI: 10.1111/j.1753-0407.2012.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and efficacy of metformin extended‐release oral antidiabetic therapy in patients with type 2 diabetes: An observational trial in Asia

Abstract: BackgroundThe aim of the present prospective observational study was to assess the tolerability and antihyperglycemic efficacy of metformin extended-release (MXR) in the routine treatment of patients with type 2 diabetes mellitus (T2DM) from six Asian countries.MethodsData from 3556 patients treated with once-daily MXR for 12 weeks, or until discontinuation, were analyzed.ResultsTreatment with MXR was well tolerated, with 97.4% of patients completing 12 weeks of treatment. Only 3.3% of patients experienced one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Lifestyle modification such as nutritional therapy, exercise, and weight loss remains the essential factor of treatment of T2DM at any stage of the disease including IGT. Since metformin is effective not only in obese patients but also in lean patients with T2DM [ 42 ], and reduces insulin demand by lowering hepatic glucose production, starting therapy by metformin in addition to lifestyle modification should be considered as early a stage of diabetes as possible in patients without contraindication. The use of incretin therapy, which enhances physiological insulin secretion without serious adverse effects, is now widely used for treatment of T2DM.…”
Section: Treatment Strategy For T2dm In Asian Populationmentioning
confidence: 99%
“…Lifestyle modification such as nutritional therapy, exercise, and weight loss remains the essential factor of treatment of T2DM at any stage of the disease including IGT. Since metformin is effective not only in obese patients but also in lean patients with T2DM [ 42 ], and reduces insulin demand by lowering hepatic glucose production, starting therapy by metformin in addition to lifestyle modification should be considered as early a stage of diabetes as possible in patients without contraindication. The use of incretin therapy, which enhances physiological insulin secretion without serious adverse effects, is now widely used for treatment of T2DM.…”
Section: Treatment Strategy For T2dm In Asian Populationmentioning
confidence: 99%
“…[1014] However, it was reported that some patients may discontinue therapy due to the higher medication costs. The disintegration time for HGCs is about 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…However, because metformin primarily relies on renal function for elimination,72 it is contraindicated in patients with renal disease or dysfunction 73. Metformin is also associated with gastrointestinal adverse effects that may lead to discontinuation for some patients but may dissipate with continued use or with dosing adjustments 74. TZDs have been shown to have beneficial effects on cognitive disorders related to insulin resistance in the central nervous system in studies in mice75 and to exert favorable effects on cardiovascular (CV) risk markers in patients with T2D 76.…”
Section: Potential Combinations To Improve Pathophysiologic Dysfunctionmentioning
confidence: 99%